EFEKTIVITAS AKUPUNTUR PADA PASIEN NYERI DI PELAYANAN KESEHATAN TRADISIONAL RUMAH SAKIT UMUM DAERAH BALI MANDARA - Brata Putri, Dhiancinantyan Windydaca; Kadek Tiana Dewi, Ni; I Putu Riska Ardinata; Ida Ayu Manik Partha Sutema (UHN IGB Sugriwa Denpasar, 2026)
Pain is a sensory experience that interferes with an individual's daily activities and functions as a protective mechanism for the body against dangerous stimuli causing damage to the body. Acupuncture has become an increasingly popular alternative therapy for managing various types of pain. The use of acupuncture therapy is used as an alternative therapy to conventional medical therapy. This study aims to identify and describe the level of pain intensity in patients receiving acupuncture therapy at the Traditional Health Service at the Bali Mandara Regional General Hospital. This study's pre-experimental design uses a one-group pretest-posttest design. This research involved 66 respondents who had different pain criteria. Before being given treatment in the form of acupuncture therapy, 50 respondents (75.8%) had severe pain and 16 respondents (24.2%) had moderate pain. After being given acupuncture therapy, 52 (78.8%) had mild pain and 14 (21.2%) showed moderate pain category. The Wilcoxon test results showed a significant difference (p = 0.000) between the pain scale before and after acupuncture therapy. This study shows that acupuncture is proven to be reduce pain intensity in various pain complaints.